Money growth and inflation: International historical evidence on high inflation episodes for developed countries - Marco Gallegati; Federico Giri; Michele Fratianni (Bank of Finland, 2019)
How long is the long run in the relationship between money growth and inflation? How important are high inflation episodes for the unit slope finding in the quantity theory of money? To answer these questions we study the relationship between excess money growth and inflation over time and across frequencies using annual data from 1871 to 2013 for several developed countries. Wavelet-based exploratory analysis shows the existence of a close stable relationship between excess money growth and inflation only over longer time horizons, i.e. periods greater than 16 and 24 years, with money growth mostly leading. When we investigate the sensitivity of the unit slope finding to inflation episodes using a scale-based panel data approach we find that low-frequency regression coefficients estimated over variable-length subsamples before and after WWII are largely affected by high inflation episodes. Taken together the results that inflationary upsurges affect regression coefficients but not the closeness of the long-run relationship call for a qualification of the Quantity Theory of Money and suggests that policymakers should not lose interest on monetary developments.
URN:NBN:fi:bof-201901101024
Keywords: C22; E40; E50; N10; 330